PERCONTOHAN PAGAR PENGAMAN RUANG TERBUKA DI KELURAHAN KALIANYAR - Maria Immaculata Ririk Winandari; Punto Wijayanto; Sri Handjajanti; Juliandini Iskandar; Aurum Obe Titu Eki (Universitas Trisakti, 2022)
Kalianyar settlement has the highest density in Indonesia. These conditions make this settlement vulnerable to fire hazards. The need for open space, the dense environmental conditions, as well as the possibility of fire hazards require residents to prepare for the disaster threat. Understanding and skills regarding the disaster mitigation development and maintenance of open space is necessary to maximize the use of space, to improve the quality of the environment, as well as the skills of citizens. Community action plan is very important to improve the environment quality. The aim of this program is to provide a safety fence based on community action plan. The method used in this program is assisting the development process. This program can optimize the use of space while improving the environment quality. Participants were neighborhood officers and residents at RT 02 RW 07. The result showed that the sense of belonging to the open space can be improved through the fence construction pilot project. The sense of belonging is shown by painting the safety fence independently by residents.